Relative influence of nitrogen induced crop parameters on yield of rice using principal component analysis model - Rishitha, S; Shankar, T; Biswas, T; Raghava, C V; Patra, P K; Sarkar , S (Plant Science Today, 2025)
Nitrogen (N) plays a crucial role in metabolic and physiological processes of rice. As a result, N causes variation in status of growth parameters, yield attributers as well as grain and straw yield of rice. Data base on various growth parameters recorded in different time and that of yield attributers can be used to work out the individual relationship of each parameter with grain or straw yield. Such statistical analysis may not yield a concrete result. However, principal component analysis (PCA) helps in identifying the principal components among the observed parameters and their relative influence on grain or straw yield. With such background a field study was carried out in southern Odisha, India; to assess the performance of different crop parameters and yield of kharif rice under seven nitrogen levels. Crop was exposed to: 0, 20, 40, 60, 80, 100 and 120 kg N ha-1. Increase in N level increases the magnitude of: plant height, total tiller number per m2, leaf area index (LAI), number of panicles bearing tiller per m2, number of spikelets per panicle, panicle length, per cent filled grains, grain and straw yield. Status of all variables increased with an increase in N level. The increment was significantly differed among the treatments, when the N level difference was 40 kg N ha-1. Principal component analysis (PCA biplot) established that, a strong performance of rice under N80 (which is the recommended dose of rice in this region) followed by N60, N100, N40, N120 and so on. The parameter, ‘panicle bearing tiller 90’ is the well representative parameter in the PCA space followed by percent filled grain and plant height.